The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1516-31802007000200008
|View full text |Cite
|
Sign up to set email alerts
|

Does sodium nitroprusside kill babies? A systematic review

Abstract: OBJECTIVE:To determine whether sodium nitroprusside causes fetal death in pregnancies complicated with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 27 publications
0
9
0
9
Order By: Relevance
“…Estes achados podem estar associados ao não diagnóstico destas morbidades entre as gestantes estudadas visto que a hipertensão e a hemorragia ainda são as principais causa de óbito materno no Brasil 30,31 . Estudo anterior realizado no município do Rio Grande observou que, apesar da cobertura pré-natal ser de 95,8% e a média de consultas ser de 7,4 consultas/gestante, quando se avalia a qualidade da atenção prestada, apenas 26,8% tem seu pré-natal classificado como adequado 32 .…”
Section: Discussionunclassified
“…Estes achados podem estar associados ao não diagnóstico destas morbidades entre as gestantes estudadas visto que a hipertensão e a hemorragia ainda são as principais causa de óbito materno no Brasil 30,31 . Estudo anterior realizado no município do Rio Grande observou que, apesar da cobertura pré-natal ser de 95,8% e a média de consultas ser de 7,4 consultas/gestante, quando se avalia a qualidade da atenção prestada, apenas 26,8% tem seu pré-natal classificado como adequado 32 .…”
Section: Discussionunclassified
“…For refractory hypertension in intensive care, higher dose diazoxide can be considered (although there is more hypotension than with labetalol) [339] as can sodium nitroprusside (being mindful of the unproven risk of fetal cyanide toxicity) [340].…”
Section: Antihypertensive Therapymentioning
confidence: 99%
“…A systematic review of literature concluded that there is insufficient evidence for definitive conclusions about any direct association between sodium nitroprusside use and fetal demise. 50 …”
Section: Nitroprussidementioning
confidence: 99%